Perbandingan Hukum Perburuhan Negara Indonesia Dengan Hukum Perburuhan Negara Singapura, Negara Malaysia, dan Negara Thailand - Dharmalinga, Inge Nur Az’zahra Maheswari (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research seeks to answer several problem formulations which include: what are the main characteristics of labor law in each ASEAN country; what are the significant similarities and differences between labor regulations in Indonesia and other ASEAN countries; and how changes in regulations through the Omnibus Law affect employment conditions in Indonesia compared to other ASEAN countries. Through this comparative analysis, the research is expected to provide in-depth insight into the effectiveness and impact of labor regulations in creating a fair and competitive work environment in the ASEAN region. Research results show that Labor Law in Indonesia, through the Job Creation Law, provides more flexibility in contracts and working conditions compared to other ASEAN countries such as Singapore, Malaysia and Thailand. These changes include adjustments to fixed-term work contracts, setting regional minimum wages, and more flexible working hours. Although occupational safety and health regulations have been strengthened, enforcement is still less stringent than in other countries that have more structured regulations.